Therapeutic plasma exchange – A brief review of indications, urgency, schedule, and technical aspects. (June 2019) - Pham, Huy P.; Staley, Elizabeth M.; Schwartz, Joseph
Abstract: The American Society for Apheresis (ASFA) regularly publishes evidence-based guidelines, with the most recent edition in 2016, to assist the requesting and/or apheresis physicians with the evaluation of therapeutic apheresis. Given that therapeutic plasma exchange (TPE) is one of the most common therapeutic apheresis procedures, in this review, we discuss the rationale of TPE in both ASFA category I (first-line therapy) and II (second-line therapy) indications. However, the ASFA Guidelines usually provide little guidance with regard to scheduling/urgency issues. Given that mobilizing resources to perform apheresis after-hours may be expensive and challenging, we classified the urgency of the procedures in this review into 3 distinct groups: emergent (i.e. TPE should be started as soon as possible, preferably within 4–6 h upon request), urgent (i.e. TPE should be initiated within 24 h of request), and routine (i.e. TPE may be performed during regular working hours) based on our experiences in clinical practices. A brief discussion of the technical aspects as well as important considerations for an apheresis consultation is also provided.